Vote buying, electoral violence and democratisation in Nigeria (2019)
This paper examines the menace of vote buying and electoral violence as recurring decimal in Nigeria’s political journey since it returned to democratic government in 1999. Nigeria has over the years witnessed incessant electoral violence which has claimed many lives and has badly affected the country’s nascent democratic experience. 1t is opined to have dented the image of the country among the comity of nations. At the beginning of the country’s democratic experience after many years of military Interregnum, Nigerians thought the civilian administration would be better as those elected or appointed as the case may be, were expected to deliver the dividends of democracy to the people who voted them into power. Existing studies on democratic governance in Nigeria have focused majorly on the historical, economic and the social effects of bad governance to the neglect of how vote buying and electoral violence could constitute a perennial clog in the wheel of progress in our efforts at sustaining our hard earned democracy. This paper therefore in clear terms makes effort to discuss the menace of vote buying and electoral violence, their consequences and how to ensure a free, fair and credible elections in Nigeria.